Energetic Arguments on the Microstructural Analysis in Ionic Liquids. Issue 7 (5th May 2021) - Kobayashi, Takeshi; Smiatek, Jens; Fyta, Maria
Abstract: The interaction of ionic liquids (ILs) with additives or impurities is crucial for the performance of ILs in technological applications. In order to understand the interaction between these, an insight onto the microscopic arrangement of molecules is needed. As a representative case, 1‐ethyl‐3‐methylimidazolium dicyanamide ([EMIM] + [DCA] − ) mixtures are studied with dimethyl sulfoxide (DMSO) and water in bulk phase using molecular dynamics (MD) simulations. Different molar fractions of DMSO and water are studied to elucidate the influence of the molecular solute concentration on the structuring of the ILs. The results indicate that DMSO‐[EMIM] + [DCA] and water‐[EMIM] + [DCA] − mixtures are defined by quite distinct molecular interactions between the species. By increasing the DMSO or water concentration, in the former the solute molecules are repelled from the ions, while in the latter they accumulate closer to the ions. The differences arise from the weakening of the interactions between the ions imposed by the presence of the water molecules whereas DMSO promotes a strengthening of these interactions. Accordingly, this study provides a deep understanding of the IL behavior in combination with neutral solute molecules and allows for a proper selection of IL‐solute combinations in view of specific technological applications. Abstract : A novel method for the analysis of microstructuring in ionic liquid solutions is discussed in terms of an effective interaction energy. This concept of a single energy term can clearly underline the distinct structural details of solutes within different ionic liquid mixtures.